The behaviour of airlines' passengers in the context of COVID-19 pandemic - Laura Diaconu (CES Working Papers, 2021)
The COVID-19 pandemic has negatively been influencing the air transport industry. The devastating impacts, which started to be felt since the first months of 2020, consisted in rationalizing the fleet, reducing staff number and reconfiguring their networks and capacity. Therefore, understanding passengers' attitudes towards travelling during a global pandemic may strengthen aviation industry practices and minimize the costs in the downturn period. Considering these aspects, the purpose of the present paper is to analyse the behaviour of airlines' leisure and business passengers in the context of the COVID-19 pandemic, by underlying those factors that may have a strong impact on their travelling attitudes. In order to achieve this purpose, we have conducted an online survey on a sample of 146 respondents from Romania.
Keywords: 330; airlines' passengers; COVID-19 pandemic; behavioral predictors